Clinical assessment in Takayasu's arteritis: major challenges and controversies - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2017)
Takayasu's arteritis (TAK) is a rare, chronic, large-vessel vasculitis (LVV) that predominantly affects aorta, its major branches and the pulmonary arteries. Recent controversial issues in the diagnosis, disease assessment and prognosis in TAK are discussed in this review. In recent years, conventional angiography, the standard method for the initial diagnosis, seems to have been replaced by the new imaging modalities, such as MRI and I8F-FDG-PET. Less invasive techniques (CT/MRI) are now suggested first, compared to conventional angiography, and MRI is preferable to CT with less contrast load! radiation. Ultrasound is useful for carotid assessment, but being a user-dependent technique, imaging of deeper vessels (subclavian and aorta) are not reliable. 18F-FDG-PET is useful especially in patients with no vascular symptomslsigns, fever of unknown origin or unexplained acute-phase response. MRI and 18F-FDG-PET are also promising for the assessment of disease activity. New tools for disease assessment, such as the Indian Takayasu Arteritis Score (ITAS2010), aim to better characterise and quantify disease activity. Prognosis is recently possibly improving with lower mortality, but a substantial damage is present even in early cases. There is a clear need to develop a validated set of outcome measures to be used in clinical trials of TAK. The OMERACT Vasculitis Working Group has taken on this task, finished a Delphi exercise with experts and aims to develop a core set of outcomes for LW.
Keywords: Takayasu's arteritis; clinical assessment; outcome; LARGE-VESSEL VASCULITIS; GIANT-CELL ARTERITIS; DISEASE-ACTIVITY; SYSTEMIC VASCULITIS; PENTRAXIN-3 LEVELS; OUTCOME MEASURES; ACTIVITY SCORE; DIAGNOSIS; FEATURES; MANAGEMENT